A method and use for preparing UiO-66 encapsulated platinum nanoparticle composite by electrostatic attraction regulation

Through electrostatic attraction, UiO-66 material is regulated, combined with core-shell structure, the problems of low dispersion and poor stability of platinum particles have been successfully solved, and efficient catalyst synthesis and reaction efficiency have been achieved.

CN116493051BActive Publication Date: 2025-02-07TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310467009.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-02-07
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

In the prior art, when synthesizing a packaging catalyst for precious metal platinum, the platinum particles have low dispersion, poor stability, and it is difficult to regulate the position of the platinum particles inside the support, affecting the diffusion of reactants and products.

Method used

The electrostatic attraction control UiO-66 material is used to change the pH of the UiO-66 dispersion, adjust the charge on the surface of the carrier, and the electrostatic attraction is used to introduce the platinum precursor into the carrier channel, and the core-shell structure is constructed to control the platinum particles in the Positioning packages in shells.

Benefits of technology

The high dispersion and stability of platinum particles are achieved, the activity and reaction efficiency of the catalyst are improved, the synthesis steps are simplified, and the diffusion path of reactants and products is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116493051B_ABST
    Figure CN116493051B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a UiO-66 encapsulated platinum nanoparticle complex by electrostatic attraction regulation. First, various types of UiO-66 materials are synthesized, including UiO-66-X (X=H, F, NH2, etc.) modified by different functional groups, and two types of UiO-66 modified by different functional groups are combined into a composite material with a core-shell structure, and UiO-66-H@UiO-66-NH2 and UiO-66-H@UiO-66-F, etc. can be obtained. Various types of UiO-66 materials are dispersed in a hydrochloric acid aqueous solution with a lower pH value, so that the UiO-66 material is positively charged as a whole. An anionic platinum compound (such as chloroplatinic acid) is used as a precursor, and is added to the dispersion of the UiO-66 material for sufficient stirring, so that the chloroplatinic acid molecules can enter the pores of the UiO-66 material through electrostatic attraction. The catalyst obtained after the obtained solution is vacuum dried is reduced at a higher temperature using a hydrogen-containing atmosphere. The present invention aims at the disadvantages of low dispersion and poor stability of platinum particles of platinum-loaded heterogeneous hydrogenation catalysts, and synthesizes an encapsulated catalyst with highly dispersed platinum nanoparticles, which has higher activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalyst synthesis, and in particular to a method for preparing a UiO-66 encapsulated platinum nanoparticle composite by regulating electrostatic attraction and use thereof. Background Art

[0002] Styrene hydrogenation is the most common hydrogenation reaction in industry. The reaction conditions are mild and it is a simple method to evaluate the catalytic hydrogenation of olefins. Ethylbenzene, the product of selective hydrogenation of styrene, has good stability and plays an important role in gasoline production and aromatics industry. Therefore, styrene hydrogenation has attracted widespread attention in the petroleum industry. Styrene hydrogenation catalysts are generally supported metal heterogeneous catalysts, in which the carrier is used to disperse the metal and provide abundant diffusion channels, and the noble metal is loaded to activate the reactants and hydrogenate. The metal organic framework UiO-66 has three-dimensional long-range ordered channels and a specific surface area of ​​up to 1000cm 2 / g, the pore size diameter is 0.8nm, and it has good chemical and thermal stability. These physical characteristics are conducive to the encapsulation loading of precious metal platinum, and have a large enrichment effect on styrene molecules. The precious metal encapsulation structure can greatly improve the stability of precious metals due to the effect of pore confinement. Platinum is generally used as the precious metal component, and the dispersion and electronic structure of platinum play a key role in improving the hydrogenation performance of the catalyst. Highly dispersed platinum can not only increase the specific surface area of ​​platinum particles and improve the utilization rate of platinum active sites, but also increase the contact interface between the metal and the carrier, and enhance the electron transfer from the metal to the carrier to obtain electron-deficient platinum particles. Electron-deficient platinum particles can enhance the interaction force with electron-rich carbon-carbon double bonds, thereby enhancing the activation of reactants and improving catalytic activity.

[0003] There are generally two methods for encapsulating precious metal platinum. One is the impregnation method, that is, directly impregnating chloroplatinic acid on the carrier, and then reducing it to platinum element at high temperature under a hydrogen atmosphere. The platinum particles synthesized by this method tend to deposit on the surface of the carrier, and the particle size is large, the dispersion is low, and the interaction between platinum and the carrier is weak, resulting in low metal utilization, activity and stability, and the catalyst performance obtained is general. The other is to pre-synthesize platinum particles, and then add the platinum particles in situ to the carrier synthesis liquid so that the carrier grows around the platinum particles. In this method, in order to overcome the resistance of heterogeneous growth of the carrier, a stabilizer is generally grafted on the surface of the platinum particles, so that some active sites are covered and the activity decreases. The synthesis conditions and preparation steps of these two methods are relatively complicated. And the position of the platinum particles inside cannot be controlled, which makes the diffusion of reactant and product molecules more complicated. In addition, for encapsulated catalysts, their longer three-dimensional pores are not conducive to the diffusion of reactant and product molecules.

[0004] In order to solve the above problems, the present invention is proposed. Summary of the invention

[0005] The present invention aims to provide a method for preparing a UiO-66 positioned encapsulated highly dispersed platinum particle catalyst by electrostatic attraction regulation, and the catalyst prepared by the method is used for the selective hydrogenation reaction of styrene compounds.

[0006] The first aspect of the present invention provides a method for preparing a UiO-66 encapsulated platinum nanoparticle composite by electrostatic attraction regulation, which comprises the following steps:

[0007] Step (1): synthesizing UiO-66-X, wherein X is H, NH2, or F;

[0008] Step (2): Dispersing the synthesized UiO-66-H in N,N-dimethylformamide solution, adding zirconium source, water, regulator, 2-aminoterephthalic acid ligand or 2,5-difluoroterephthalic acid ligand to the dispersion in sequence, and ultrasonically homogenizing, stirring at 100-120° C. for 8-12 hours to obtain UiO-66-H@UiO-66-NH2 or UiO-66-H@UiO-66-F;

[0009] Step (3): Chloroplatinic acid loading

[0010] Add appropriate amount of water to UiO-66-H, UiO-66-NH2, UiO-66-F, UiO-66-H@UiO-66-NH2, and UiO-66-H@UiO-66-F respectively and disperse them evenly, add a small amount of hydrochloric acid dropwise to adjust the pH of the solution to 1-7, add an aqueous solution of chloroplatinic acid, stir well at room temperature for 8-12 hours, and dry in a vacuum oven at 50-65°C overnight; reduce in an atmosphere containing hydrogen at 200-300°C to obtain the target catalyst.

[0011] Preferably, the specific steps of synthesizing UiO-66-X in step (1) are as follows:

[0012] Add zirconium source, water, N,N-dimethylformamide, regulator, and ligand to the crystallization kettle in sequence, and mix them uniformly with ultrasound, and crystallize them at 100-120° C. for 12-24 hours; wash and centrifuge with N,N-dimethylformamide and acetone in sequence, and dry at 100-120° C. to obtain the product UiO-66-X;

[0013] When the added ligand is terephthalic acid, the obtained product is UiO-66-H; when the added ligand is 2-aminoterephthalic acid, the obtained product is UiO-66-NH2; when the added ligand is 2,5-difluoroterephthalic acid, the obtained product is UiO-66-F.

[0014] Preferably, the zirconium source in step (1) is zirconium tetrachloride or zirconium oxychloride.

[0015] Preferably, the regulating agent in step (1) is formic acid or acetic acid.

[0016] Preferably, the molar ratio of the zirconium source, water, regulator and ligand in step (1) and step (2) is in the range of:

[0017]

[0018]

[0019] Where BDC stands for ligand and M stands for modulator.

[0020] Preferably, the mass ratio of the aqueous solution of chloroplatinic acid added in step (3) to UiO-66-X, UiO-66-H@UiO-66-NH2, and UiO-66-H@UiO-66-F is (0.01-0.02):1.

[0021] Preferably, the hydrogen-containing atmosphere in step (3) is 10% H2 / 90% Ar, 20% H2 / 80% Ar, or 100% H2.

[0022] The second aspect of the present invention provides an application of the catalyst prepared by the method described in the first aspect in the selective hydrogenation reaction of styrene compounds.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention uses chloroplatinic acid as a precursor, makes the UiO-66 material positively charged under low pH conditions, introduces the platinum precursor into the carrier pores through electrostatic attraction with chloroplatinic acid, and obtains UiO-66 encapsulating small-size and highly dispersed electron-deficient platinum nanoparticles through reduction in a hydrogen-containing atmosphere.

[0025] 2. In the present invention, the chloroplatinic acid molecules have electrostatic attraction with the core and shell of the core-shell materials UiO-66-H@UiO-66-NH2 (UiO-66-NH2 is the shell, UiO-66-H is the core) and UiO-66-H@UiO-66-F (UiO-66-F is the shell, UiO-66-H is the core) under low pH conditions. The amino group in UiO-66-H@UiO-66-NH2 forms NH3 +There is a stronger electrostatic attraction between chloroplatinic acid and chloroplatinic acid, which can selectively anchor chloroplatinic acid in UiO-66-NH2. UiO-66-F in UiO-66-H@UiO-66-F has stronger hydrophobicity, which will reduce the infiltration rate of chloroplatinic acid aqueous solution inside the carrier, and can selectively retain chloroplatinic acid in UiO-66-F. Therefore, by utilizing the difference in the interaction force between the core and shell in the chloroplatinic acid molecule and the core-shell structure, chloroplatinic acid can be regulated and loaded in the shell layer, realizing the controllable loading of platinum particles.

[0026] 3. The present invention adjusts the surface charge of the UiO-66 material by changing the pH of the UiO-66 dispersion, and utilizes the electrostatic attraction between the carrier and chloroplatinic acid to achieve the encapsulation of platinum particles inside the pores, so as to achieve better dispersion and stability effects.

[0027] 4. The present invention further constructs a core-shell structure and utilizes the difference in interaction force between chloroplatinic acid and the core and the shell to achieve positioning and packaging of platinum particles in the shell.

[0028] 5. The present invention aims at the disadvantages of low dispersion and poor stability of platinum particles in platinum-loaded heterogeneous hydrogenation catalysts, and synthesizes an encapsulated catalyst with highly dispersed platinum nanoparticles, which has high activity and stability. In addition, the method constructs a core-shell carrier structure, and uses the difference in the strength of the core and shell forces between chloroplatinic acid and the core-shell structure to control the internal binding position of chloroplatinic acid, thereby controlling the loading of platinum nanoparticles in the shell layer of the carrier, shortening the diffusion distance of reactants and products, and improving the diffusion rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 TEM images of comparative example (a) and embodiment 1 (bd);

[0030] Figure 2 XPS spectra of Comparative Example (a) and Example 1 (b-d);

[0031] Figure 3 TEM image of Example 2;

[0032] Figure 4 TEM images of Example 3(a), Example 4(b) and Example 5(c);

[0033] Figure 5 The results of the styrene hydrogenation reaction of the comparative example and Example 1;

[0034] Figure 6 The results of the styrene hydrogenation reaction of Example 2. DETAILED DESCRIPTION

[0035] The following examples illustrate the process described in the present invention, but the present invention is not limited to these examples.

[0036] Example 1: (add hydrochloric acid to adjust pH to 1)

[0037] 100 mg of UiO-66-H, UiO-66-NH2, and UiO-66-F were ultrasonically dispersed in 30 mL of water, and 187.5 μL of hydrochloric acid aqueous solution (concentration of 8 mol / L) was added to adjust the pH to 1, and the mixture was stirred thoroughly. Then 23.6 mL of chloroplatinic acid aqueous solution (0.87 mmol / L) was added to the UiO-66-X dispersion, stirred at 25 ° C for 12 h, and then vacuum evaporated at 60 ° C until the liquid was evaporated to dryness, and dried in a vacuum oven at 60 ° C overnight. Finally, the powder was reduced at 200 ° C for 2 h in a 10% H2 / 90% Ar atmosphere. According to the analysis of the slice TEM images, the platinum nanoparticles on the obtained catalyst are uniformly loaded in the entire interior of UiO-66-H, UiO-66-NH2 and UiO-66-F, with a diameter of about 1.97nm. The catalysts are named Pt@UiO-66-H, Pt@UiO-66-NH2 and Pt@UiO-66-F. XPS analysis shows that the degree of electron deficiency of platinum particles is: Pt@UiO-66-F>Pt@UiO-66-H>Pt@UiO-66-NH2.

[0038] Example 2: (core-shell material as carrier)

[0039] The specific implementation conditions are similar to those in Example 1, but with UiO-66-H@UiO-66-NH2 and UiO-66-H@UiO-66-F as carriers. According to the slice TEM image analysis, in the core-shell materials UiO-66-H@UiO-66-NH2 and UiO-66-H@UiO-66-F, the platinum particles are uniformly loaded in the shell part, that is, inside UiO-66-NH2 and inside UiO-66-F, and the particle diameter is about 2nm. The two catalysts are named Pt@UiO-66-H@UiO-66-NH2 and Pt@UiO-66-H@UiO-66-F, respectively.

[0040] Example 3: (Add hydrochloric acid to adjust pH to 3)

[0041] The specific implementation conditions are similar to those in Example 1, but UiO-66-H is used as the carrier, and the amount of hydrochloric acid added is reduced to adjust the pH to 3. From the TEM image, it can be seen that there are particles loaded on the surface of UiO-66-H, and the complete encapsulation of platinum particles cannot be achieved. The dispersion of platinum particles is lower than that in Example 1.

[0042] Example 4: (Increasing the pore size of the carrier)

[0043] The specific implementation conditions are similar to those in Example 1, but UiO-66-H with a larger pore size is used as the carrier. The obtained catalyst was analyzed by TEM, and it was found that there was serious aggregation of platinum particles on the surface of UiO-66-H, and the particle diameter was about 30nm.

[0044] Example 5: (Pure hydrogen reduction)

[0045] The specific implementation conditions are similar to those in Example 1, but the reducing atmosphere is pure hydrogen gas. The obtained catalyst was analyzed by TEM, and it was found that there were serious platinum particles aggregated on the surface of UiO-66-H, and the particle diameter was about 8nm.

[0046] Example 6: (Adjusting the core-shell structure)

[0047] The specific implementation conditions are similar to those in Example 1, but UiO-66-NH2@UiO-66-H (UiO-66-H as shell and UiO-66-NH2 as core) is used as the carrier.

[0048] According to the analysis of the slice TEM images, the platinum particles are uniformly loaded in the core region of the core-shell structure, and no particles are loaded in the shell region. This indicates that adjusting the composition of the core-shell structure can selectively adjust the loading position of the platinum particles.

[0049] Comparative Example: (without adding hydrochloric acid)

[0050] Except that hydrochloric acid was not added and UiO-66-H was used as the carrier, the other synthesis conditions were the same as those in Example 1.

[0051] It can be seen from the TEM image that the diameter of the obtained catalyst platinum nanoparticles is about 10nm. The dispersion of platinum particles is lower than that in Example 1, and there are particles loaded on the surface of UiO-66-H, and the encapsulation of platinum particles cannot be achieved. The obtained catalyst is named Pt / UiO-66-H. XPS analysis shows that compared with Pt / UiO-66-H, the platinum in Pt@UiO-66-H has a higher binding energy, indicating that the encapsulation structure can better adjust the electronic state of platinum to electron-deficient, which is beneficial to the activation of electron-rich carbon-carbon double bonds.

[0052] Example 7: Synthesis of UiO-66 Material

[0053] 360 mg ZrCl4, 0.3 mL water, 60 mL N, N-dimethylformamide, 3 mL acetic acid, and 258 mg ligand were added to the crystallization kettle in sequence, and ultrasonically homogenized, and crystallized at 120°C for 12 hours; 30 mL N, N-dimethylformamide and 30 mL acetone were used in sequence for washing and centrifugation 5 times, and dried at 120°C. The obtained product is UiO-66-X.

[0054] The synthesized 100 mg UiO-66-H was dispersed in 10 mL N,N-dimethylformamide solution, and 50 mg ZrCl4, 0.05 mL water, 0.4 mL acetic acid, and 35.8 mg 2-aminoterephthalic acid ligand or 2,5-difluoroterephthalic acid ligand were added to the dispersion in sequence, and ultrasonically homogenized. The mixture was stirred at 120 °C for 8 h to obtain UiO-66-H@UiO-66-NH2 or UiO-66-H@UiO-66-F.

[0055] Example 8: Styrene hydrogenation reaction

[0056] The Pt@UiO-66-H, Pt@UiO-66-NH2 and Pt@UiO-66-F obtained in Example 1, the Pt@UiO-66-H@UiO-66-NH2, Pt@UiO-66-H@UiO-66-F obtained in Example 2 and the Pt / UiO-66-H obtained in the comparative example were respectively applied to the catalytic hydrogenation reaction of styrene. The reaction conditions were: pressure 0.1 MPa, temperature 25°C, and a molar ratio of styrene to platinum of 150.

[0057] The results of catalytic hydrogenation are shown in Table 1. As can be seen from Table 1, the hydrogenation rate of the Pt@UiO-66-H catalyst is greatly improved compared with the Pt / UiO-66-H catalyst. The catalytic activity of Pt@UiO-66-F, which has a hydrophobic surface and a more electron-deficient platinum species, is better than that of Pt@UiO-66-H and Pt@UiO-66-NH2. The above results show that the UiO-66 catalyst encapsulating highly dispersed platinum particles prepared by the present invention is applied to the saturated hydrogenation reaction of styrene. Due to its high metal dispersion, platinum species with low electron density and superior reactant enrichment, efficient hydrogenation conversion of styrene can be achieved. In addition, the hydrogenation activities of Pt@UiO-66-H@UiO-66-NH2 and Pt@UiO-66-H@UiO-66-F catalysts are increased by 2.13 times and 10.2 times respectively compared with Pt@UiO-66-H. This indicates that the controllable metal loading position effectively improves the diffusion resistance of reactants and products and further enhances the hydrogenation activity.

[0058] Table 1 Comparison of catalytic performance results

[0059]

Claims

1. A method for preparing a UiO-66 encapsulated platinum nanoparticle composite by electrostatic attraction regulation, characterized in that: It includes the following steps: Step (1): synthesizing UiO-66-X, wherein X is H or F; Step (2): Disperse the synthesized UiO-66-H in N,N-dimethylformamide solution, add zirconium source, water, regulator, 2-aminoterephthalic acid ligand or 2,5-difluoroterephthalic acid ligand to the dispersion in sequence, and mix by ultrasonication, and stir at 100-120°C for 8-12 hours to obtain UiO-66-H@UiO-66-NH2 or UiO-66-H@UiO-66-F; Step (3): Chloroplatinic acid loading Add appropriate amount of water to UiO-66-F, UiO-66-H@UiO-66-NH2, and UiO-66-H@UiO-66-F respectively and disperse them evenly, add a small amount of hydrochloric acid dropwise to adjust the pH of the solution to 1-7, add an aqueous solution of chloroplatinic acid, stir thoroughly at room temperature for 8-12 h, and then dry in a vacuum oven at 50-65°C overnight; reduce in an atmosphere containing hydrogen at 200-300°C to obtain the target catalyst.

2. The method according to claim 1, characterized in that The specific steps of synthesizing UiO-66-X in step (1) are as follows: Add zirconium source, water, N,N-dimethylformamide, regulator, and ligand to the crystallization kettle in sequence, and make them uniform by ultrasonication, and crystallize them at 100-120°C for 12-24 hours; wash and centrifuge with N,N-dimethylformamide and acetone in sequence, and dry at 100-120°C to obtain the product UiO-66-X; When the added ligand is terephthalic acid, the obtained product is UiO-66-H; when the added ligand is 2,5-difluoroterephthalic acid, the obtained product is UiO-66-F.

3. The method according to claim 2, characterized in that The zirconium source described in step (1) is zirconium tetrachloride or zirconium oxychloride.

4. The method according to claim 2, characterized in that: The regulating agent in step (1) is formic acid or acetic acid.

5. The method according to claim 1, characterized in that The molar ratio of the zirconium source, water, regulator and ligand in step (1) and step (2) is as follows: Zr / BDC is 1.0-1.54; H2O / Zr is 5.0-13.0; M / Zr is 22.0-45.0, wherein BDC represents the ligand and M represents the regulator.

6. The method according to claim 1, characterized in that The mass ratio of the aqueous solution of chloroplatinic acid added in step (3) to UiO-66-F, UiO-66-H@UiO-66-NH2, and UiO-66-H@UiO-66-F is (0.01-0.02):

1.

7. The method according to claim 1, characterized in that The hydrogen-containing atmosphere in step (3) has a volume ratio of 10% H2 / 90% Ar or 20% H2 / 80% Ar.

8. Use of the catalyst prepared by the method according to claim 1 in the selective hydrogenation reaction of styrene compounds.

Citation Information

Patent Citations

  • Transition metal copper loaded UiO-66-NH2 composite catalyst, preparation method and application thereof

    CN106378194A

  • Preparation and application of Pd / UiO-66 by strong electrostatic adsorption method

    CN113663736A